Risking Returns: Moving from Public to Private Equity - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2010)
The notion of risk identifies a project that matches with the risk appetite of an entrepreneur not necessarily the investors. This can explain why entrepreneurs would start up companies but it cannot explain why ex-post the investors continue, given that a diversified portfolio of publicly traded assets could potentially generate similar return with lower risk. We re-evaluate the evidence through performance measures using relative probability distributions of public and private equity funds, and identify the nature of the deviations. We observe that the heterogeneity in different investor classes are greatly reduced using standard covariates to identify the choice between public and private equity funds.